Self-consistency of polarization diversity measurement of rainfall - Scarchilli, G., author; Chandrasekar, V., author; Gorgucci, E., author; Dobaie, A., author; IEEE, publisher (Colorado State University. Libraries, 1996)
Polarization diversity measurements of rainfall, namely the reflectivity factor, differential reflectivity, and specific differential propagation phase, vary in a constrained three-dimensional space. Algorithms are derived to quantify this self-consistency of measurements. In particular, estimation of the specific differential propagation phase shift based on reflectivity and differential reflectivity is analyzed in detail. Theoretical simulation as well as radar observations of rainfall at S (CSU-CHILL) and C (Polar 55C) bands are used to demonstrate that the range profiles of differential propagation shift can be constructed from measurements. of reflectivity and differential reflectivity.